Issues and Strategies of Agile Methodology Adoption in Remote Working Environment: A Systematic Literature Review - Chairina Marsya; Raharjo, Teguh (AI Society & STMIK Indonesia, 2024)
Agile and remote work are two topics that are currently popular in the business world, especially in the information technology industry. Both have been implemented in several companies, but Covid-19 has made it more widely used. Even though remote work offers many conveniences such as saving transport time and flexibility of place, it contrasts with Agile which requires intense collaboration and communication. Some of the obstacles found in previous research were that the team had fewer opportunities for communication, a lot of time was spent on meetings, so it was easy to get distracted when working remotely. This study uses a Systematic Literature Review to answer what are the obstacles and strategies in adopting agile in remote work systems. This research found that, there are five majors factors that effected while implement remote agile; coordination, response to change, leadership, facilitating condition, and policies & guidelines.